SAT0626 Anakinra treatment in refractory cases of adult-onset still disease: case series. (12th June 2018) - Ugurlu, S.; Yurttas, B.; Guzelant, G.; Ergezen, B.; Ozdogan, H.
Abstract : Background: Despite methotrexate and steroid treatment, in cases of Adult-onset Still's disease (AOSD) it is usually difficult to maintain clinic stability. In refractory cases, Anakinra treatment has been reported to be efficacious. 1 Objectives: In this retrospective review, it is aimed to evaluate the AOSD cases treated with anakinra in our centre. Methods: Fourteen AOSD patients (11 female, 3 male) who were being followed in our outpatient clinic were reviewed retrospectively. The demographic characteristics, pre- and post-treatment clinical findings were reported. Results: The mean follow-up period of the patient population was 33.5±30.07 months (mean ±SD). Initial prednisolone dose was 37.3 mg/day. Except for one, all of our patients were exposed to methotrexate before being treated with anakinra. This patient was being treated with cyclosporine instead, since she had concomitant Macrophage Activation Syndrome. The other medications, the patients were previously treated with, were Etanercept (n=2), Tocilizumab (n=3), Infliximab (n=1) and Adalimumab (n=1). All patients were on 100 mgs of Anakinra, daily, except for the one treated with 200 mg/day. The mean duration of Anakinra therapy was 11.4 months. Among 7 patients in whom anakinra therapy was terminated, 1 had drug induced urticaria, 1 was primary irresponsive, 4 were secondary irresponsive and the other had severe pneumonia. Primary irresponsiveness is the lack of response to the therapy since the drug was first introduced, whereas in secondary irresponsiveness the case responds to the medication for a while and starts to flare again after asymptom-free period on the medication. Among 14, 7 of our patients are still on 100 mg/d Anakinra. The mean level of C reactive protein (CRP) measures was reduced from 64.38±61.95 mg/L to 34.3±24.3 mg/L with Anakinra therapy(p=0.003). Similarly, mean Erythrocyte Sedimentation Rate (ESR) was dropped to 33±22 mm/h from 59±35 mm/h by the help of the therapy(p<0.001). Among patients who primarily responded Anakinra therapy the mean Ferritin measures dropped to 427.25 ng/ml from 910 ng/ml (p=0.006). On the other hand, the Ferritin level was not significantly reduced in patients who did not respond Anakinra.The mean Patient reported Global Visual Analogue Scale (PG-VAS) score was also decreased to 3.83±4.7 from 9.5±0.07 following the therapy(p<0.001). Unfortunately, one of our 7 patients who were followed in remission under Anakinra died of an unknown etiology. Conclusions: Adult-onset Still's disease is a challenging disorder, lacking a sufficient long-time clinical control. In order to obtain a full remission, various efforts have been spent so far. One of these approaches is to treat refractory cases with Anakinra, an IL-1 blocking agent. According to our clinical experience we state that, anakinra has a relatively high efficacy in controlling refractory cases. Reference: [1] Ortiz-Sanjuán F, et al. Efficacy of Anakinra in RefractoryAdult-OnsetStill'sDisease: MulticenterStudyof 41 PatientsandLiteratureReview. Medicine(Baltimore)2015Sep;94(39):e1554. Disclosure of Interest: None declared